The new theatre of the struggle for EU unity: Judicial cooperation in criminal matters and police cooperation confronts member state sovereignty - Lukić Maja (Anali Pravnog Fakulteta u Beogradu)
Most institutions that play crucial role in enforcement of EU law regulating judicial cooperation in criminal matters and police cooperation today had existed before the enactment of the Lisbon Treaty, which transformed the nature of European legislation in that area from intergovernmental to supranational. The Lisbon Treaty afforded judicial cooperation in criminal matters and police cooperation a pronounced idiosyncrasy: the greatest degree of flexibility of Member State participation. The experience gained in applying the mechanism of enhanced cooperation, including the concept of the European public order, contributes to the utility of the entire body of law on judicial cooperation in criminal matters and police cooperation as the new unifying factor of the EU.